bcl-2 expression in non-Hodgkin's lymphomas is not associated with bcl-2 gene rearrangements - Papakonstantinou, Georgios; Verbeke, Caroline Sophie; Hastka, Jan; Bohrer, Manfred H.; Hehlmann, Rüdiger (British journal of haematology, 2001)
Previous reports have associated bcl-2 gene rearrangements found in non-Hodgkin's lymphomas with an inappropriately elevated bcl-2 expression compared with the mature B-cell stage of development. This study investigates bcl-2 expression in non-Hodgkin's lymphomas (NHL) without bcl-2 gene rearrangements. Molecular analysis in 168 patients with NHL revealed 45 patients without bcl-2 gene rearrangements in which additional immunostaining for bcl-2 protein was possible. An unexpectedly high prevalence (39/45) of bcl-2 expression was found. The levels and patterns of bcl-2 expression were not specific for the histological type of NHL and were similar to those shown in comparable cases with bcl-2 gene rearrangements. In conclusion, bcl-2 expression is not specific for NHL bearing bcl-2 gene rearrangements. This finding implicates the existence of other deregulating control mechanisms of bcl-2 expression, more important than bcl-2 gene rearrangements.
Elektronische Reproduktion der Druckausgabe
Gesehen am 17.05.2022